THE EFFECT OF COMPETITIVENESS TOWARD ECONOMIC PERFORMANCE IN REGENCIES / CITIES AT EAST JAVA - Suliswanto, Muhammad Sri Wahyudi; -, Sutikno (KINERJA, 2019)
This research is intended to analyze the competitiveness of regions to economic performance in each district/city in East Java Province. This research uses regression tool of panel data with approach of random effect model. The results of this study indicate that the indicators that have a big role on economic performance are the aspect of public services. So the priority of policy in general is the improvement of public service in terms of order of regulation/regulation, provision of infrastructure, and readiness of human resources. Improving the quality of human resources should also be a priority because based on the results of research indicates that variable human resources is an important factor in the formation of competitiveness.Keywords: competitiveness, economic performance, East Java.